Niacin ameliorates ulcerative colitis via prostaglandin D2‐mediated D prostanoid receptor 1 activation. Issue 5 (27th March 2017) - Li, Juanjuan; Kong, Deping; Wang, Qi; Wu, Wei; Tang, Yanping; Bai, Tingting; Guo, Liang; Wei, Lumin; Zhang, Qianqian; Yu, Yu; Qian, Yuting; Zuo, Shengkai; et al.
Abstract: Niacin, as an antidyslipidemic drug, elicits a strong flushing response by release of prostaglandin (PG) D2 . However, whether niacin is beneficial for inflammatory bowel disease (IBD) remains unclear. Here, we observed niacin administration‐enhanced PGD2 production in colon tissues in dextran sulfate sodium (DSS)‐challenged mice, and protected mice against DSS or 2, 4, 6‐trinitrobenzene sulfonic acid (TNBS)‐induced colitis in D prostanoid receptor 1 (DP1)‐dependent manner. Specific ablation of DP1 receptor in vascular endothelial cells, colonic epithelium, and myeloid cells augmented DSS/TNBS‐induced colitis in mice through increasing vascular permeability, promoting apoptosis of epithelial cells, and stimulating pro‐inflammatory cytokine secretion of macrophages, respectively. Niacin treatment improved vascular permeability, reduced apoptotic epithelial cells, promoted epithelial cell update, and suppressed pro‐inflammatory gene expression of macrophages. Moreover, treatment with niacin‐containing retention enema effectively promoted UC clinical remission and mucosal healing in patients with moderately active disease. Therefore, niacin displayed multiple beneficial effects on DSS/TNBS‐induced colitis in mice by activation of PGD2 /DP1 axis. The potential efficacy of niacin in management of IBD warrants further investigation. Synopsis: Niacin, an ancient lipid‐lowering drug that elicits a strong flushing response through release of prostaglandin (PG) D2 . Niacin improves experimentally induced ulcerative colitis in mice and humans through the activation of PGD2 /DP1 axis. Niacin increases PGD2 release in both mice and humans. Niacin confers protection against DSS/TNBS‐induced colitis in mice through DP1‐mediated inhibition of vascular leakage, suppression of colonic epithelium apoptosis, and reduction of pro‐inflammatory cytokine secretion. Retention enema treatment containing niacin effectively promotes clinical remission and mucosal healing in patients with moderately active UC. Abstract : Niacin, an ancient lipid‐lowering drug that elicits a strong flushing response through release of prostaglandin (PG) D2 . Niacin improves experimentally induced ulcerative colitis in mice and humans through the activation of PGD2 /DP1 axis.